this part of a big problem

do i distribute the 3 first or do i distribute the 4 first?

-3(n-3).4

Results 1 to 2 of 2

- January 29th 2007, 01:51 AM #1

- Joined
- Oct 2006
- Posts
- 21

- January 29th 2007, 02:06 AM #2

- Joined
- Apr 2005
- Posts
- 1,631

-3(n -3).4

If that is

-3(n -3)(4),

then it does not matter whether you multiply by the -3 first or by the 4 first.

If by the -3 first:

-3(n -3)(4)

= (-3n +9)(4)

= -12n +36 -------------answer.

If by the 4 first:

-3(n -3)(4)

= -3(4n -12)

= -12n +36 ----------same as above.